More than a glitch : confronting race, gender, and ability bias in tech - Broussard, Meredith (Cambridge : The MIT Press, 2023)
"Broussard argues that the structural inequalities reproduced in algorithmic systems are no glitch. They are part of the system design. This book shows how everyday technologies embody racist, sexist, and ableist ideas; how they produce discriminatory and harmful outcomes; and how this can be challenged and changed"--
Understanding machine bias -- Recognizing bias in facial recognition -- Machine fairness and the justice system -- Real students, imaginary grades -- Ability and technology -- Gender rights and databases -- Diagnosing racism -- An AI told me I had cancer -- Creating public interest technology -- Potential reboot.
Includes bibliographical references and index.
Keywords: Technology -- Social aspects; Data processing -- Social aspects; Artificial intelligence -- Social aspects; Discrimination; Software failures